Transforming societies : capacity-building and skills transfer - Chin, Yvonne (Commonwealth Secretariat LondonGB, 2007)
Highlights CFTC's assistance to Commonwealth countries in capacity building in areas such as trade, managing debt, public service delivery, sustainable development, social transformation and human rights.